Game Theory Dalam Penentuan Strategi Pemasaran Optimal Dalam (Studi Kasus Persaingan E-Commerce Shopee dan TokoPedia) - Praditya, Al-Farrel Raka; Prasetyo, Sri Yulianto Joko (TIN: Terapan Informatika Nusantara, 2021)
The development of information technology in the field of online business continues to increase. This causes the internet to become a coincidence that cannot be separated from society. Developments that cause people to use it for business activities. Businesses in the digital industry continue to compete to meet people's needs instantly. Meeting the needs of e-commerce businesses to customers with many users is an important thing for companies to pay attention to the quality of their services. This is what creates competition between Shopee and Tokopedia e-commerce. So, this research was made using the Game Theory method and assisted using IBM's SPSS to determine customer satisfaction in terms of interface design, completeness of goods and prices offered by both Shopee and Tokopedia e-commerce. There are several factors that support the rapid growth of the e-commerce sector in Indonesia. First, the increasing number of smartphones and the internet. Second, the size of the population. Third, Indonesia has a lot of young people who are technology literate, which means they are quick to adapt to new things, in this case, new technology.